Anxiety in exams and learning strategies in secondary students in Lima Metropolitan - Alegre, Alberto A. (2013)
This study sought to determine the relationship between test anxiety and learning strategies among students of 4th and 5th grade of secondary of public schools in Lima. The sample was obtained by an intentional method, evaluating 469 students, 45.6% males and 54.4% females, belonging to four public schools of Lima. It was used the questionnaire of Anxiety and performance - CAR and the Learning Strategies Scale - ACRA. The test anxiety (punctuations in all three dimensions: concern, emotionality and facilitation) and learning strategies (punctuations in four dimensions: acquisition, coding, support and recovery of information processing) had low correlations and in some cases negative, all of which are significant.